The Role of Uterine and Umbilical Arterial Doppler in High-risk Pregnancy: A Prospective Observational Study from India - Teena Nagar; Deepak Sharma; Mukesh Choudhary; Shusheela Khoiwal; Rajendra Prasad Nagar; Aakash Pandita (SAGE Publishing, 2015)
Aim To study the role of Doppler imaging in prediction of high-risk pregnancies and their outcomes. Methods and Material This prospective study in a setup of tertiary-level care center includes 500 high-risk pregnant women from rural and urban sectors and evaluates the predictive values of various Doppler indices. Results Out of 500 patients, 110 patients had abnormal Doppler among them, 70 patients had abnormal uterine artery Doppler, and 50 patients had abnormal umbilical artery Doppler flow indices. In all, 10 patients had both umbilical artery and uterine artery abnormal Doppler indices. When uterine artery was abnormal (70 patients), 20 patients had preeclampsia, 10 patients had pregnancy-induced hypertension (PIH), and 25 patients had intrauterine growth restriction (IUGR). Systolic/diastolic (S/D) ratio and notch had sensitivity of 60% and positive predictive value of 33.3% and 37.5%, respectively. When umbilical artery was abnormal (50 patients), 10 had preeclampsia, 15 had PIH, and 15 had IUGR. S/D ratio had the highest positive predictive value of 40%; sensitivity is same for all. In uterine artery, combination of parameters had the best sensitivity of 80%, followed by notch and S/D ratio. In umbilical artery, combination of parameters, S/D ratio, and RI (resistance index) had sensitivity of 40%; specificity of all the indices was 91-96%. In all, 20 patients had bilateral notch, and among them 15 developed preeclampsia and 15 developed IUGR. When both uterine and umbilical artery Doppler were abnormal (10 patients), all patients had preeclampsia and IUGR. Conclusion Therefore, Doppler study may be used for the prediction of preeclampsia and IUGR to reduce the maternal and perinatal morbidity and mortality.